2004
DOI: 10.1155/2004/763030
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray tandem mass spectrometric measurements of organotin compounds

Abstract: Electrospray mass spectrometry of a series of organotin compounds in solutions of methanol are reported. Low energy collision‒induced dissociation MS/MS analysis of diagnostic precursor ions confirmed the characteristic fingerprint patterns obtained in the conventional electrospray spectra and proved to be a specific and very sensitive method for quantification of the (R3Sn)2O and the series of RnSnX4–ncompounds in environmental matrices. Concentrations of butyltin compounds (TBTX, DBTX2and MBTX3) in sediment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…The spectrum also indicated the formation of the fragment ion centred at m / z 717 assigned as [(Ph 3 Sn) 2 OH] + , which is obtained probably as the hydrolysis product of [Ph 3 Sn] + ion, and the radical cation [SnH 2 ] +• at m / z 122. The diagnostic fragment ions observed in the mass spectra of complexes 1 and 2 have been reported previously for several complexes containing the R 2 Sn(IV) 2+ moiety …”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The spectrum also indicated the formation of the fragment ion centred at m / z 717 assigned as [(Ph 3 Sn) 2 OH] + , which is obtained probably as the hydrolysis product of [Ph 3 Sn] + ion, and the radical cation [SnH 2 ] +• at m / z 122. The diagnostic fragment ions observed in the mass spectra of complexes 1 and 2 have been reported previously for several complexes containing the R 2 Sn(IV) 2+ moiety …”
Section: Resultssupporting
confidence: 76%
“…The characteristic fragment ions along with their relative abundance and probable ion structure are presented in Section and also summarized in Tables S4 and S5. The m / z values discussed have been assigned on the basis of 120 Sn, which is the most abundant isotope of tin …”
Section: Resultsmentioning
confidence: 99%
“…5). These results go hand in hand with earlier findings of Banaub et al (2004) and clearly revealed that K. pneumoniae strain SD9 biotransforms TBTCl into DBTCl 2 and finally into MBTCl 3 by utilizing it as a sole carbon source in MSM.…”
Section: Mass Spectrometric Analysis Of the Biotransformation Productsupporting
confidence: 81%
“…The TBT fragmentation pattern had been described previously (Banoub et al 2004;Békri et al 2006). On the basis of the optimized product ions of TBT, the predicted MRM LC-MS/MS methods were developed using LightSight TM software and applied for the screening of possible metabolites.…”
Section: Tbt Qualitative Analysismentioning
confidence: 99%